Regulatory T cells are less sensitive to glucocorticoid hormone induced apoptosis than CD4(+) T cells - Prenek, Lilla (Apoptosis, 2020)
Earlier we have reported that thymic regulatory T cells (Treg) are resistant to in vivo glucocorticoid hormone (GC)-induced apoptosis, while the most GC-sensitive DP thymocytes died through the activation of mitochondrial apoptotic pathway. Here we analyzed the apoptosis-inducing effect of high dose (10(–6) M) in vitro dexamethasone (DX) treatment in mouse thymic- and splenic Tregs and CD4(+) T cells. Activation of both extrinsic and intrinsic apoptotic pathways started after 2 h of DX treatment in CD4 SP thymocytes and was 3 × higher than in CD4(+) splenocytes, while in Treg cells, weak activation of the extrinsic apoptotic pathway started only after 3 h. We also investigated the expression of 21 apoptosis-related molecules using a protein array and found higher level of both pro-and anti-apoptotic molecules in Tregs compared to CD4(+) T cells. 4 h in vitro DX treatment induced upregulation of most apoptosis-related molecules both in Tregs and CD4(+) T cells, except for the decrease of Bcl-2 expression in CD4(+) T cells. We found high basal cytosolic Ca(2+) levels in untreated Treg cells, which further increased after DX treatment, while the specific TCR-induced Ca(2+) signal was lower in Tregs than in CD4(+) T cells. Our results suggest that in the background of the relative apoptosis resistance of Treg cells to GCs might be their high basal cytosolic Ca(2+) level and upregulated Bcl-2 expression. In contrast, downregulation of Bcl-2 expression in CD4(+) T cells can explain their higher, DX-induced apoptosis sensitivity.